Invasive Candidiasis Prevalence Among Patients in IntensiveCare Unit, Hasan Sadikin Hospital - Maulana, Hafizh Ridwan; Sumardi, Uun; Koesoemadinata, Raspati C. (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Intensive care unit (ICU) patients have a high risk of invasive candidiasis (IC), which increase mortality and prolong length of stay in hospitals, resulting greater costs. This study aimed to determine the prevalence of IC and associated risk factors in ICU patients. Methods. A cross-sectional study was conducted including medical records of patients treated in ICU Hasan Sadikin Hospital Bandung admitted in June 2016-June 2017 whose blood sample were sent for culture. The prevalence of IC and corresponding 95% confidence interval (95% CI) was determined. A case-control study was done comparing the characteristics of patients with positive culture for Candida (cases) with those who have a negative culture admitted to ICU in the same week as the cases (control), with ratio 1 to 4. Multivariate analysis was performed to determine the adjusted odds ratio (AOR), 95% CI, and p value. Results. Blood cultures were performed on 313 ICU patients. The prevalence of IC was 3.5% (95%CI: 1.8-6.2), and 9 patients died. There were 8 cases and 33 controls with complete data to be compared. Characteristics associated with invasive candidiasis were: use of ventilator more than 6 days (AOR=15.52; 95%CI: 1.51-159.15; p=0.021); use of urine catheter more than 8 days (AOR=10.77; 95%CI: 1.05-110.86; p=0.046); and positive sputum culture for Candida (AOR=9.54; 95%CI: 1.44- 63.44; p=0.020). Conclusions. Invasive candidiasis has a high mortality rate. Long-term use of ventilator and urine cathether, and positive sputum culture result were important risk factors for IC among adult patients in ICU.